Site-directed mutagenesis of mouse steroid 7 alpha-hydroxylase (cytochrome P-450(7) alpha): role of residue-209 in determining steroid-cytochrome P-450 interaction. - Iwasaki, M (1993)
We have cloned a cDNA encoding mouse steroid 7 alpha-hydroxylase P450(7) alpha (cytochrome P-450(7) alpha) and expressed it in Saccharomyces cerevisiae. Mouse P450(7) alpha is 70% identical in its amino acid sequence with the mouse steroid 15 alpha-hydroxylase P450(15) alpha (2A4). The Leu at position 209 of P450(15) alpha is the most important residue to determine the steroid hydroxylase activity of the P450 [Lindberg and Negishi (1989) Nature (London) 339, 632-634]. The P450(7) alpha contains Asn at the position corresponding to the Leu-209 of P450(15) alpha, although both P450s hydroxylate testosterone. The CO-reduced P450(7) alpha complex is unstable, so that it is quickly converted into the inactive P420, whereas the P450(15) alpha is very stable. The P450(7) alpha, however, is stabilized either by addition of testosterone or by a mutation of Asn-209 to Leu. The mutant P450(7) alpha displays a 17-fold lower Vmax. value than the wild-type enzyme. Unexpectedly, it also has 3-fold lower Km and Kd values. Residue 209 in P450(7) alpha, therefore, appears to be located at a critical site of the haem-substrate-binding pocket. Corticosterone inhibits the testosterone 7 alpha-hydroxylase activity of the wild-type P450(7) alpha, whereas it does not inhibit the mutant P450(7) alpha. Conversely, the P450(15) alpha activity becomes inhibited by corticosterone upon the replacement of Leu-209 by Asn. In addition, this mutation increases the corticosterone 15 alpha-hydroxylase activity of P450(15) alpha at least 20-fold. Whereas the inhibition by corticosterone depends on the presence of Asn at position 209, deoxycorticosterone inhibits the activities of the P450s regardless of the type of residue at 209. The results indicate, therefore, that the identity of residue 209 determines the affinity as well as specificity of steroid binding to both P450(7) alpha and P450(15) alpha.